Chinese Studies in Ukrainian Philosophy of the Soviet Period - Rudenko, Sergii; Liashenko, Iryna (Studia Warmińskie, 2020)
This paper presents the results of the authors’ study of the perception of Ancient Chinese philosophy in the Ukrainian philosophy of the Soviet period in the second half of the 20th century. The study is based on a unique source: a monograph by two authoritative and influential Soviet philosophers, Volodymyr Dmytrychenko and Volodymyr Shynkaruk, which was published in Ukrainian in 1958. The authors described the way of perception of Ancient Chinese philosophy, its ideological principles, main problems and key personalities in the Ukrainian philosophy of the Soviet period, and systematically presented them. The paper presents the authors’ conclusions about the leading theoretical positions and methodology of the history of philosophy in the Ukrainian philosophical culture of the Soviet period. The authors concluded that the peculiarity of the development of studies in the history of philosophy in Ukraine in the Soviet era is a departure from Hegel’s theory of the history of philosophy, the main theoretical and methodological shortcoming of which is “Eurocentrism”. This circumstance allows us to assert a critical rethinking of Hegel’s theory of the history of philosophy in the Ukrainian philosophical culture of the Soviet period of the second half of the 20th century. Also, in this paper, the authors prove the point of view that a comparative approach and reception studies are effective methods of studying the history of Ukrainian philosophy of the Soviet period.